2017
DOI: 10.1159/000486241
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Dopamine Mediated by β-Adrenergic Receptors in Human Keratinocytes and Macrophages: Potential Implication in Wound Healing

Abstract: Objective: Dopamine is an immunomodulatory neurotransmitter. In the skin, keratinocytes and macrophages produce proinflammatory cytokines and metalloproteinases (MMPs) which participate in wound healing. These cells have a catecholaminergic system that modulates skin pathophysiologic processes. We have demonstrated that dopamine modulates cytokine production in keratinocytes via dopaminergic and adrenergic receptors (ARs). The aim of this study was to evaluate the effect of dopamine and its interaction with β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Several lines of evidence support this conclusion: (1) In vitro studies demonstrated that DA both binds and signals via α 2 -adrenergic receptors, albeit at lower affinities than NE 46,[78][79][80] . (2) DA has been shown to signal via immune cell and cardiac β-adrenergic receptors 81,82 . 3Computational modeling studies demonstrate strong structural homologies between DA's interactions at binding sites of adrenergic receptors and D 2 -like receptors 46,83 .…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support this conclusion: (1) In vitro studies demonstrated that DA both binds and signals via α 2 -adrenergic receptors, albeit at lower affinities than NE 46,[78][79][80] . (2) DA has been shown to signal via immune cell and cardiac β-adrenergic receptors 81,82 . 3Computational modeling studies demonstrate strong structural homologies between DA's interactions at binding sites of adrenergic receptors and D 2 -like receptors 46,83 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that dopamine affects wound healing by delaying cell migration through its effect on propranolol, which is known to affect cell migration and angiogenesis. Furthermore, dopamine seems to decrease the MMP-9 activity systemically, but increases MMP-9 activity in macrophages 18 . One study has shown that GLC756, a dopamine D2 agonist and D1 antagonist, has an anti-inflammatory effect on dermal fibroblasts, further implicating dopa-mine as a key modulator of wound healing and scar formation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dopamine seems to decrease the MMP-9 activity systemically, but increases MMP-9 activity in macrophages. 18 One study has shown that GLC756, a dopamine D2 agonist and D1 antagonist, has an antiinflammatory effect on dermal fibroblasts, further implicating dopamine as a key modulator of wound healing and scar formation. 19 Collectively, these studies suggest that catecholamines have multiple potential complex effects on the responses to cutaneous injury.…”
Section: Discussionmentioning
confidence: 99%
“…CBDV is a partial agonist of dopamine D2-like receptors [100]. It has been shown recently that D2-like receptor agonism in the skin, promotes the recovery of the skin barrier and wound healing [101][102][103].…”
Section: Cannabinoidsmentioning
confidence: 99%